Quantum squeezing induced nonreciprocal enhancement of optomechanical cooling - Lu, Tian-Xiang; Chen, Liu-Sha; Zhong, Wo-Jun; Xiao, Xing (Frontiers in Physics, 2023)
We theoretically propose how to achieve nonreciprocal enhancement of mechanical cooling in a compound cavity optomechanical system composed of an optomechanical resonator and a χ (2) -nonlinear resonator. By parametric pumping the χ (2) -nonlinear resonator unidirectionally with a classical coherent field, quantum squeezing of the resonator mode emerges in one direction but not in the other, resulting in asymmetric optical detuning and a tunable chiral photon interaction between two resonators. As a result, nonreciprocal mechanical cooling is achieved. More importantly, enhanced mechanical cooling deep into the ground-state can be achieved in the selected directions due to the squeezing effect. These results provide an experimentally feasible way to realize nonreciprocal ground-state cooling of mechanical resonator, which may have a wide range of applications in quantum communication and quantum technologies.